2020
DOI: 10.1038/s41598-020-64306-8
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of auditory spatial judgments in the visually impaired is dependent on sound source distance

Abstract: Blindness leads to substantial enhancements in many auditory abilities, and deficits in others. It is unknown how severe visual losses need to be before changes in auditory abilities occur, or whether the relationship between severity of visual loss and changes in auditory abilities is proportional and systematic. Here we show that greater severity of visual loss is associated with increased auditory judgments of distance and room size. on average participants with severe visual losses perceived sounds to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Després, Candas, and Dufour (2005c) showed that near-sighted and amblyopic participants performed better in a self-positioning task than normally sighted controls. Kolarik et al (2020) investigated the effect of severity of visual loss on auditory distance judgments using stimuli with simulated distances from 1.2 to 13.8 m. Sighted controls and participants with a range of visual losses (groups with mild, mid-range, and severe loss) were tested in simulated anechoic and reverberant environments using speech, music and noise stimuli.…”
Section: The Effects Of Partial Visual Loss On Auditory Abilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Després, Candas, and Dufour (2005c) showed that near-sighted and amblyopic participants performed better in a self-positioning task than normally sighted controls. Kolarik et al (2020) investigated the effect of severity of visual loss on auditory distance judgments using stimuli with simulated distances from 1.2 to 13.8 m. Sighted controls and participants with a range of visual losses (groups with mild, mid-range, and severe loss) were tested in simulated anechoic and reverberant environments using speech, music and noise stimuli.…”
Section: The Effects Of Partial Visual Loss On Auditory Abilitiesmentioning
confidence: 99%
“…For localization in azimuth, blindness in one eye is associated with enhancement (Hoover, et al, 2012), while central visual loss in both eyes is associated with degradation (Lessard, et al, 1998). Severe visual loss is associated with reduced accuracy in judging the distance of closer sounds and increased accuracy for farther sounds, reflecting systematic changes in the mapping between simulated and perceived distance (Kolarik, et al, 2020). Further studies are needed to clarify the effects of the type of visual loss on hearing, such as monocular blindness with one unimpaired eye or central or peripheral visual loss.…”
Section: The Effects Of Partial Visual Loss On Auditory Abilitiesmentioning
confidence: 99%
“…For statistical analysis, data were grouped into near (1.22-1.72 m), middle (2.44-4.88 m), and far (6.90-13.79 m) distances. This procedure was similar to that used by Kolarik et al (2020), which followed the methods utilized by Voss et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…These advances have enabled the use of virtualization techniques to explore a range of issues, including how reverberation affects speech understanding (Ellis & Zahorik, 2019), and how the availability of visual depth information increases the accuracy of auditory estimates of distance within a room (Anderson & Zahorik, 2014). How audition provides spatial information for judgments of the distance of sound sources (Bidart & Lavandier, 2016; Kolarik, Cirstea, & Pardhan, 2013a, 2013b; Zahorik, 2002) and room size (Kolarik, Pardhan, et al., 2013; Kolarik et al., 2020) has also been investigated using virtualization techniques. Audition provides valuable spatial information when vision is unavailable and is critical for spatial awareness and navigation by blind people.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation methods have been described in our previous studies investigating auditory 171 judgments of distance (Kolarik et al 2013a, b;Kolarik et al 2013c;Kolarik et al 2017a) and room size (Kolarik et al 2013d;Kolarik et al 2020). In the current study, the virtualization was made more realistic by convolving sound reflections with the appropriate head-related transfer functions (HRTFs) in addition to doing this for the direct sound component (Culling et al 2013;Culling 2013;Moore et al 2016).…”
mentioning
confidence: 99%